Investment Decision Making for Indonesian Gen Z in the Islamic Capital Market - Wijayanti, Farah Nur Syafi'ah; Cahya Ningrum, Anisa Risqi; Wicaksana, Ragil Satria; Purbowisanti, Ratih (JESI (Jurnal Ekonomi Syariah Indonesia), 2025)
Introduction: The rapid growth of Indonesia’s Islamic capital market, particularly in the Special Region of Yogyakarta (DIY), is driven by technological advancements, improved investment literacy, and psychological factors such as financial self-efficacy. As digital natives, Generation Z holds significant potential to become Sharia-compliant investors. This study examines the effects of technological advancement, investment knowledge, and financial self-efficacy on investment decisions in the Islamic capital market, with investment interest serving as a mediating variable, grounded in the Theory of Planned Behavior (TPB).Methods: A causal-associative quantitative approach was employed, involving 100 Generation Z respondents in DIY who had prior experience in Islamic capital market transactions. Respondents were selected through purposive sampling, and data were collected via an online questionnaire. Data analysis utilized Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate both direct and indirect relationships between variables.Results: Findings indicate that technological advancement, investment knowledge, and financial self-efficacy each have a significant positive effect on investment decisions. Technological advancement and financial self-efficacy also significantly and positively influence investment interest, while investment knowledge does not significantly affect investment interest. Moreover, investment interest mediates the relationship between technological advancement and financial self-efficacy with investment decisions, but not between investment knowledge and investment decisions. Measurement model assessment confirmed reliability and validity, with composite reliability exceeding 0.7 and Average Variance Extracted (AVE) values above 0.5.Conclusion: Technological advancement and financial self-efficacy are key drivers of both interest and decision-making among Generation Z investors in the Islamic capital market. In contrast, investment knowledge tends to directly influence decisions without enhancing interest. These findings highlight the importance of leveraging technology and strengthening financial confidence through practical education. Market regulators and industry players can use these insights to design targeted literacy programs and campaigns aimed at engaging young investors.